HIL real-time simulator based 3D-space vector pulse width modulation for performance analysis of 3-phase matrix converter - Palanisamy, R.; Shanmugasundaram, V.; Lakshmi, M.; Karthikeyan, B.; Aboras, Kareem M.; Bajaj, Mohit; Alsharef, Mohammad; Elattar, Ehab E.; Kamel, Salah (Frontiers in Energy Research, 2022)
In this paper, Three Dimensional Space Vector Pulse Width Modulation (3D-SVPWM) is developed to obtain the performance analysis of a 3-phase matrix converter (MC). MC is used to convert 3-phase fixed AC voltage to 3-phase variable AC voltage, which provides superior performance compared to conventional AC to AC converters. The 9-bidirectional power switches in a 3-phase matrix converter are controlled by appropriate gating pulses utilizing 3D-SVPWM. In conventional AC to AC power converters, the common mode voltage is induced across the load terminal, which causes bearing failure and EMI issues and so leads to increased total harmonic distortion (THD). Implementing the 3D-SVPWM approach with the nearest switching state vector (NSV) selection mechanism alleviates these problems. The output findings of the simulation and real-time simulator are verified using the Matlab Simulink model and the HIL real-time (OPAL-RT) simulator.